2011
DOI: 10.1111/j.1468-3083.2011.04338.x
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphisms of toll‐like receptor‐4 protect against acne conglobata

Abstract: Carriage of gene SNPs is protective against the development of acne conglobata even in the presence of P. acnes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 16 publications
0
14
0
1
Order By: Relevance
“…From the total of 191 patients enrolled in the already described cohort [6], assays were run successfully in 185 to be analysed in the present study. The demographic characteristics of the study population are shown in table 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From the total of 191 patients enrolled in the already described cohort [6], assays were run successfully in 185 to be analysed in the present study. The demographic characteristics of the study population are shown in table 2.…”
Section: Resultsmentioning
confidence: 99%
“…This case-control study was conducted throughout the period from September 2009 until January 2011 [6]. The study protocol was reviewed and approved by the Ethics Committee of Attikon University General Hospital.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the individual genes responsible for this high heritability remain unclear. Although candidate gene-based studies have identified a few genetic variants associated with acne in tumor necrosis factor alpha ( TNFα ) (Al-Shobaili et al 2012; Baz et al 2008; Szabo et al 2011), tumor necrosis factor receptor 2(TNFR2) (Tian et al 2010), interleukin-1A ( IL1A ) (Szabo et al 2010), cytochrome P450, family 17 (CYP17) (He et al 2006), toll-like receptor 2(TLR2) (Tian et al 2010) and toll-like receptor 4 ( TLR4 ) (Grech et al 2012), no genome-wide association studies (GWASs) have been reported on this common skin condition. To identify novel genetic variants for acne, we conducted a genome-wide association study on severe teenage acne within a U.S cohort of young females, the Nurses’ Health Study II (NHSII).…”
Section: Introductionmentioning
confidence: 99%
“…Pobudzenie receptora TLR2 przez P. acnes na keratynocytach warstwy podstawnej, lejka i gruczołów łojowych powoduje uwolnienie IL1α, co prowadzi do nadmiernego rogowacenia ujść mieszków włosowych 7 dni po aktywacji [79]. Wykazano, że polimorfizm pojedynczego nukleotydu (SNP) genu receptora TLR4 chroni przed rozwojem trądziku skupionego [80]. Stosowane w leczeniu trądziku zwykłego miejscowe retinoidy zmniejszają stan zapalny poprzez zmniejszenie ekspresji receptorów TLR2 na monocytach, natomiast sole cynku hamują ekspresję TLR2 na keratynocytach [81,82].…”
Section: Inne Choroby Skóryunclassified